1997
DOI: 10.1007/s004120050240
|View full text |Cite
|
Sign up to set email alerts
|

Centromeric inactivation in a dicentric human Y;21 translocation chromosome

Abstract: A de novo dicentric Y;21 (q11.23;p11) translocation chromosome with one of its two centromeres inactive has provided the opportunity to study the relationship between centromeric inactivation, the organization of alphoid satellite DNA and the distribution of CENP-C. The proband, a male with minor features of Down's syndrome, had a major cell line with 45 chromosomes including a single copy of the translocation chromosome, and a minor one with 46 chromosomes including two copies of the translocation chromosome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 39 publications
4
28
0
Order By: Relevance
“…A likely explanation for this is that dicentric chromosomes are unstable. These products can comigrate to the same pole during mitosis (38,87,102), inactivate one of the centromeres (2,12,32,39,102), or undergo additional cycles of rearrangements during mitosis (59,60,65,67). Checkpoint defects would allow cells to progress through the cell cycle in the presence of such broken chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…A likely explanation for this is that dicentric chromosomes are unstable. These products can comigrate to the same pole during mitosis (38,87,102), inactivate one of the centromeres (2,12,32,39,102), or undergo additional cycles of rearrangements during mitosis (59,60,65,67). Checkpoint defects would allow cells to progress through the cell cycle in the presence of such broken chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic modifications might differentiate the 180-bp repeat clusters. Inactivation of one centromere on dicentric chromosomes has been reported for humans (27,28), maize (29), and for barley centromeres in wheat chromosomes (30). Although the mechanism of centromere inactivation remains unclear, these phenomena imply that the DNA sequences alone are insufficient to trigger inactivation and that epigenetic marks are necessary for maintaining centromere function.…”
Section: As Indicated By Mcclintockmentioning
confidence: 99%
“…However, the presence of alphoid DNA is not sufficient to create a functional centromere structure. On stable dicentric chromosomes, CENP-A, CENP-C and CENP-E [a kinesin-like motor protein found at the kinetochore (Yen et al, 1991;Wood et al, 1997)] do not assemble on the inactive centromere despite the presence of alphoid DNA and CENP-B (Sullivan and Schwartz, 1995;Warburton et al, 1997;Fisher et al, 1997). A marker chromosome containing a neocentromere, which lacks detectable alphoid DNA and CENP-B (du Sart et al, 1997), was found to be mitotically stable, and most of the known centromere proteins assembled at the site of the neocentromere (Saffery et al, 2000).…”
Section: Introductionmentioning
confidence: 99%